A Study of the Understanding of Key Concepts of Electromagnetism of 11th Grade Greek High School Students - Kaliampos, G.; Pantidos, P.; Kalogiannakis, M.; Ravanis, K. (Jurnal Pendidikan IPA Indonesia, 2021)
This study is set in the context of teaching and learning about electromagnetism in Greek high schools. Drawing from constructivism theory, the study aspires to explore students’ understandings of key concepts on both electric and magnetic field as well as electromagnetic induction. For this purpose, an experimental investigation was conducted with 80 11nth grade high school students. Empirical data was collected through a questionnaire which was developed on the basis of test subjects used on past exams in Greek high schools in electromagnetism area. Research findings suggest that students face difficulties in dealing with qualitative tasks in electric and magnetic field. In addition, they seem to confront severe difficulties in conceptualizing the notion of induction of emf.